Muscle bioenergetics and metabolic control at altitude - Cerretelli, P.; Marzorati, M.; Marconi, C. (High Altitude Medicine & Biology, 2009)
High altitude functional data, particularly those obtained on humans in the field by conventional techniques, appear to be often affected by a large variability that does not seem to be justified by the characteristics of the research protocols and by the adopted experimental procedures which, in most cases, are "state of the art". This is also evident by the frequent occurrence of debates (e.g. "point - counterpoint" contributions by specialists in the Journal of Applied Physiology) on issues whose interpretation was taken for granted. The appearance of an exclusive new player, the multi-gene transcription protein Hypoxia Inducible Factor (HIF-1) recognized as the master regulator of cell hypoxic signaling, opens a new scenario. Indeed, among the genes regulated by HIF-1, besides those expressing EPO and VEGF controlling erythropoiesis and angiogenesis, respectively, there are hundreds of other genes whose products play a large number of metabolic and transport functions. The aim of the present work is to revisit some earlier results that have been generally overlooked, in order to provide them with a more comprehensive interpretation. This has been done on the basis of work on cell hypoxic signaling including some metabolic players recently identified by muscle proteome analysis. Particular emphasis has been laid on the molecular interpretation of findings such as improved metabolic efficiency of locomotion in chronic hypoxia, origin and significance of an apparent misnomer such as the so-called "lactate paradox", and the physiological meaning of the muscle mitochondrial mass reduction in both altitude natives and acclimatized lowlanders.